2011
DOI: 10.1007/s11244-011-9642-9
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Low-Coordination Gold Sites on Au(111) Surface by 1,4-phenylene Diisocyanide Adsorption

Abstract: The adsorption of CO on a saturated overlayer of 1,4-phenylene diisocyanide (PDI) adsorbed on a Au(111) surface at 300 K is studied using scanning tunneling microscopy (STM), density functional theory (DFT) calculations and reflection absorption infrared spectroscopy (RAIRS). The PDI forms closed-packed rows of gold-PDI chains by extracting gold atoms from the Au(111) substrate. They are imaged by STM and the structure calculated by DFT. The adsorption of CO is studied on the low-coordination gold sites formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
61
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 57 publications
(105 reference statements)
11
61
3
Order By: Relevance
“…PDI Binding and Morphology on Au(111). The long 1-D chains observed in the STM image in Figure 2b and c are similar to those recently reported by Boscoboinik et al, for PDI deposited and imaged at 300 K on a Au(111) surface at both very low coverage (∼0.004 ML) 24 and saturated coverage 25. In their…”
supporting
confidence: 90%
“…PDI Binding and Morphology on Au(111). The long 1-D chains observed in the STM image in Figure 2b and c are similar to those recently reported by Boscoboinik et al, for PDI deposited and imaged at 300 K on a Au(111) surface at both very low coverage (∼0.004 ML) 24 and saturated coverage 25. In their…”
supporting
confidence: 90%
“…[15][16][17] The relatively short (B1.1 nm) repeat distance between gold atoms in the oligomer suggests the possibility of being able to chemically bond between gold nanoparticles with various separations by incorporating a number of repeat units until the gap is bridged. PDI has been previously proposed as a prototypical molecular electronic component, 4,6,[18][19][20][21] and theory suggests that PDI is a suitable candidate for device applications.…”
mentioning
confidence: 99%
“…S2 (ESI †). 15 A maximum activation energy of B0.8 eV is estimated for this process by assuming that the partition functions in the initial and transition states are equal yielding an Arrhenius pre-exponential factor (kT/h) of B10 13 s À1 . In fact, the hopping rate could be higher if more events had occurred that were not observed within the time resolution of our experiment.…”
mentioning
confidence: 99%
“…This is longer than that observed for PDI chains on Au(111), 11.7±0.2 Å, by approximately the length of an extra phenyl ring (see Figure 3). 17,18,24 The correlation between the monomer length and molecular dimensions supports an adsorption geometry in which BPDI molecules lie parallel (or nearly so) to the surface. Since abutting -NC terminal groups are not likely to be chemically linked, diisocyanide chain formation would require a common surface binding site for both terminal -NC groups.…”
Section: A Adsorption Structuresmentioning
confidence: 76%
“…13 By contrast, recent scanning tunneling microscopy (STM) experiments showed that 1,4-phenyldiisocyanide (PDI) deposited from the vapor onto a Au(111) surface at room temperature forms one-dimensional (1D) molecular chain structures. 17,18 The proposed adsorption model for this molecular chain involves alternating PDI molecules and Au adatoms, i.e., a repeating [-PDI-Au-] monomer unit. In this structure, the PDI molecules lie flat on the surface and are bonded at each end to Au-adatoms, which originate from step edges or the Au(111) surface reconstruction.…”
Section: Introductionmentioning
confidence: 99%